DEVELOPMENT OF MATHEMATICS MODULE ON FRACTIONAL NUMBERS FOR FIFTH GRADE ELEMENTARY SCHOOL STUDENTS - Hengkang Bara Saputro (Universitas Ahmad Dahlan, 2021)
In elementary mathematics learning there is fractional number material. This material has a level of difficulty that is quite challenging in learning. The concept of fractions is taught as much as possible by using more realistic and contextual concepts and minimizing abstract teaching. In abstract mathematics learning, students need tools in the form of media and teaching materials that can clarify what will be conveyed by the teacher so that students understand and understand more quickly. This study aims to (1) develop a mathematics module on fractions for elementary school students; (2) determine the feasibility of the mathematics module on the developed fraction material. This study applies a design research type of development study. The stages carried out in the design research type of development study are: (1) Preliminary research, (2) Prototyping stage, (3) Summative evaluation, and (4) Systematic reflection and documentation. The instruments used in this study were a validation questionnaire by experts and a student response questionnaire. This research has resulted in a module developed in the form of a mathematics module on fractional number material for fifth grade elementary school students to improve students' mathematical literacy which refers to the 2013 revised 2018 curriculum. The feasibility of the developed module is very feasible with an average eligibility percentage of 93.6%. The practicality of the module used is very practical with an average practicality percentage of 94.34%.